Related party transactions and firm value: The moderating role of corporate social responsibility reporting - Tifanny Dwijaya Hendratama; Zuni Barokah (China Journal of Accounting Research, 2020)
This study investigates the influence of related party transactions (RPTs) on firm value. Further, it examines whether a firm's corporate social responsibility (CSR) reporting reflects its corporate values and ethical concerns, therefore mitigating the value-destroying effects of RPTs. Based on 274 observations from publicly listed firms in Indonesia, our results show that RPTs (i.e., related party sales) are negatively related to firm value. Further, we find that in the presence of better CSR reporting, the relationship between RPTs and firm value becomes more positive. This is in line with the view that CSR reporting, which reflects firms' ethical concerns, may serve as a mechanism against managers' opportunism. However, we find that related party payables have a positive relationship with firm value. Further investigation reveals that, although certain RPTs show a short-term, value-enhancing effect, these transactions seem to result in subsequent tunneling activities, suggesting managerial opportunism in the long term.
Keywords: 650; CSR; Ethics; Firm value; Indonesia; Related party transaction; Tunneling